SERVICE TEST OF AIRCRAFT MAINTENANCE WORKSTAND S-3 - ARMY ARCTIC TEST CENTER FORT GREELY ALASKA (1961)
The test workstand was used in the normal maintenance of seven different Army aircraft for a period of four months. Ambient temperatures during the test period ranged from 19 F to -35 F. The test workstand was satisfactory with respect to physical characteristics, functional suitability, and maintenance. The test workstand was satisfactory with respect to reliability and durability at ambient temperatures below -15 F. The test workstand was readily towed by a 1/4ton truck, easily manhandled, and was stable when stability jacks were extended. No adverse safety features were encountered and erection time required approximately 6 minutes. It is concluded that the Aircraft Maintenance Workstand S-3 should be suitable for Army use under arctic winter conditions when the deficiency listed has been corrected. (Author)